Identification of Labors’ Role Transition Processes: From Traditional to Electric Vehicles in Nepal - Galaju, Chandra Kumar (Journal of Technical and Vocational Education and Training, 2025)
The maturity of technological innovation and declining battery costs have made us opt for purchasing the electrical vehicles. It has resulted into growing preference towards electric vehicle over traditional cars, thereby spurring more job vacancies in the electric vehicle industry. The study examined the labor’s role in the transition process towards working with electric vehicle from traditional vehicle. An inductive narrative research approach was used to gather the necessary primary information from automobile technicians and engineers from authorized national electric vehicles distributors in Kathmandu. Globally, shifting towards the electric vehicles has stimulated a significant transformation in the automobile industry worldwide, which has encouraged labors of automobile to shift towards working with electric vehicle anticipating a better job opportunity in the changing automobile landscape and career sustainability. However, the experience of the role transition was not flawless. Challenges of role transition such as innovative technology and unavailability of quality training and hindrance in the shifting process caused the need for re-skilling for mitigating problems. As a result transition has presented a significant lift in the career of the participants which helped them fit in the new role. Finally, this case study serves as evidence to the transformative potential of education and institutional determination in transitioning labor’s role from the traditional to electric vehicles. However, this study does not analyze the downside of transition process and status of job demand versus job loss in the changing automobile industry.